2007
DOI: 10.1007/s10562-007-9238-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nanoscale Ceria–Platinum Composite Electrodes for Direct Alcohol Electro-Oxidation

Abstract: A nanocrystalline Pt/CeO 2 composite electrode is fabricated to study the electrochemical oxidation of methanol and ethanol. Three different methods have been developed for the preparation of the composite electrode and are compared in terms of their oxidation efficiencies. In general, all the electrode preparation methodologies show a great enhancement of the oxidation current for the alcohol. However, methods based on the electrodeposition of a ceria rich Pt matrix show the greatest effectiveness of alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 36 publications
(39 reference statements)
2
10
0
1
Order By: Relevance
“…As reported by other authors [8][9][10][11] the superior activity for methanol oxidation of Pt-Rare Earth/C compared to Pt/C electrocatalyst probably could be attributed to the bi-functional mechanism where Pt acts on methanol adsorption and dissociation and the Rare Earths provide oxygenated species at lower potentials for oxidative removal of adsorbed CO.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…As reported by other authors [8][9][10][11] the superior activity for methanol oxidation of Pt-Rare Earth/C compared to Pt/C electrocatalyst probably could be attributed to the bi-functional mechanism where Pt acts on methanol adsorption and dissociation and the Rare Earths provide oxygenated species at lower potentials for oxidative removal of adsorbed CO.…”
Section: Resultssupporting
confidence: 56%
“…The electrooxidation of methanol was studied using cyclic voltammetry and chronoamperometry in acid medium and the results showed that all PtLnO x /C (except for NdO x ) have better performance than Pt/C. Díaz et al [9] prepared different Pt/CeO 2 composite electrodes to study the electrochemical oxidation of methanol and ethanol and concluded that ceria appears to be an effective alternative to ruthenium in direct alcohol fuel cells. The enhancement of alcohol oxidation by CeO 2 was explained by two mechanisms: by inhibiting CO adsorption or by ceria oxygen storage capacity playing a role to ease the oxidation of adsorbed CO. Takahashi et al [10] synthesized Pt-CeO 2 /C using a combined process of precipitation and co-impregnation methods and investigated the activity for methanol oxidation using electrochemical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies also show that the Pt−CeO 2 catalyst is better than Pt in oxidizing methanol. 232,233 The catalyst system containing CeO 2 should be necessarily designed for good interactions with Pt nanoparticles to minimize side effects generated from the low electron conductivity of CeO 2 . Coating CeO 2 by carbonization of β-cyclodextrin was found to greatly enhance the electron conductivity.…”
Section: Effect Of Ceomentioning
confidence: 99%
“…Since platinum is a valuable material, an obvious approach is to find a catalyst that incorporates the smallest amount of platinum while giving the best performance or output voltage possible. Different researchers have found that electrodes with Pt as the principal component with other metals, oxides and non-metals enhanced the catalytic activity for methanol electrooxidation [15].…”
Section: Introductionmentioning
confidence: 99%